Decline in Wage Inequality in Brazil : A Survey - Firpo, Sergio; Portella, Alysson (World Bank, Washington, DC, 2019)
In the last decades, Brazil experienced a historical decline in its wage inequality level, particularly in the first decade of the 21st century. This paper reviews the literature that attempted to explain the observed pattern. It considers mechanisms related to the supply and demand for labor, as well as institutional factors. The paper argues that the favorable economic environment in the period, combined with increases in the minimum wage, higher formalization, and a larger supply of skilled workers led to a compression in wages. However, some aspects of the decline in wage inequality are still unanswered, such as the causes behind a reduction in the experience premium and interfirm payment heterogeneity, as well as the exact role of technological changes. The paper concludes by discussing future trends in wage inequality in Brazil.